Bioaccumulation of heavy metals in fish species from the Meiliang Bay, Taihu Lake, China - Rajeshkumar, Sivakumar; Li, Xiaoyu (Toxicology reports, 2018)
[Display omitted] •Pb, Cr, Cu and Cd concentration low level in fish muscle from Meiliang Bay, Lake Taihu.•High levels of Pb and Cu were found in liver and gills of two fish Cyprinus carpio and Pelteobagrus fluvidrac from Meiliang Bay, Lake Taihu.•The seasonal metal bioaccumulation pattern was mainly associated with fish species.•Pb, Cr, Cu and Cd mainly originate from anthropogenic sources. In the present study, the bioaccumulation of heavy metals (Cr, Cu, Cd, Pb) content were determined in freshwater edible fishes Cyprinus carpio Linnaeus and Pelteobagrus fluvidraco, which were caught from the Meiliang Bay, Taihu Lake, a large, shallow and eutrophic lake of China. The results showed that the Cr, Cu, Cd and Pb content in the edible parts of the two fish species were much lower than Chinese Food Health Criterion (1994). However, the results showed marked differences in the four analyzed metal content between the two species and different tissues as well as significant variations. Pb content were the highest in the liver of fishes, Cd contents were almost the same in all organs of fishes, Cr contents mainly enriched in the kidney and liver, Cu contents were the highest in gills, However, the total metal bioaccumulation were greatest in the liver, gills and the lowest in the muscle. Although the total accumulations were highest in P. fluvidraco compare then C.carpio. This investigation indicated that fish products in Meiliang Bay, Taihu Lake were still safe for human consumption, but the amount consumed should be controlled under the Chinese Food Health Criterion to avoid excessive intake of Pb. Further, this is the first report on seasonal distribution of heavy metals and proximate compositions of commercialized important edible fishes from Meiliang Bay, Taihu Lake, China.